COAL PILLAR STRENGTH PREDICTION CONSIDERING THE EFFECT OF INTERFACE FRICTION - Alen Irnawan - Nim: 12114021 , Muhammad
In underground coal mines, factor of safety is important. Efforts to improve the safety factor are carried out while maintaining economic factors. One of the efforts is to leave a number of coal at underground mine openings as pillars. Therefore, the value of coal mined will decrease. A precise calculation of the pillar dimension of both safety and economic aspects is required. To determine the exact dimension of the pillar, empirical equations have been developed to calculate the strength of pillars based on their dimensions. Of course, the strength of the pillars is not only determined by dimensional variables only. There are other aspects that determine the strength of coal pillars, one of the aspects is the interface friction. By considering the interface friction, of course, the design of pillars can be optimized in terms of both safety and economy aspects. The research was conducted to determine the coal pillar strength prediction equation based on uniaxial compressive strength test with variation of interface friction. From the uniaxial compressive test data of coal with high and low interface friction, linear and power regression is applied to the data. There are two forms of equations for each interface friction. To determine the best coal pillar strength prediction equation, four analysis were conducted. Those analysis are based on correlation, gradient of pillar strength increase, coal pillar model, and case study of coal pillar.